A Novel way to Reprioritize Cloud Computing Process Requests with Extended Parameters using ANN - Chopra, Pooja; Bedi, R. P. S (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing is one of the most promising technology. When using hybrid cloud we all don’t know in which order the processes will be submitted to the private and public cloud. As some processes need to be more secure than other processes. Private Cloud is meant for security and privacy than public cloud. They need some mechanism that how these processes will be executed on private cloud or public cloud. So better is to prioritize the processes. A novel way is presented where an Artificial Neural Network model is designed to reprioritize the cloud computing processes with extended parameters. ANN being an Artificial Intelligence Technique is meant for accuracy. The results shows that the proposed technique helps in improving accuracy.